To Design and Develop Fe-Cu-C Alloying Suitable for Self Lubricating Bearing through Powder Metallurgy (P/M) Technique - Azrul Nizam Bin Othman, Azrul Nizam (2008)
This project basically based on literature review and experimental basis where to give understanding to student about powder metallurgy (PM) and also to achieve the objectives.